2015
DOI: 10.1080/15384101.2015.1007751
|View full text |Cite
|
Sign up to set email alerts
|

Engagement of DYRK2 in proper control for cell division

Abstract: Dysregulation of cell cycle machinery causes abnormal cell division, leading to cancer development. To drive cell cycle properly, expression levels of cell cycle regulators are tightly regulated through the cell cycle. Dual specificity tyrosine phosphorylation-regulated kinase 2 (DYRK2) is a Ser/Thr kinase, and its intracellular functions had not been elucidated for decades. Recent studies have shown that DYRK2 downregulates key molecules on cell cycle control. This review mainly highlights the DYRK2 function … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 27 publications
1
29
0
Order By: Relevance
“…Ser46 phosphorylation triggers the induction of apoptosis-related genes, as shown in Figure 1 phosphorylation of p53 at Ser46 by DYRK2 regulates apoptotic cell death in response to DNA damage. 1,19 Previous findings also showed that p53 was phosphorylated by PKCδ in MCF7 and U2OS cells upon exposure to genotoxic agents ( Figure 4). 7 PKCδ-mediated phosphorylation was required for the interaction of PKCδ with p53.…”
Section: Ser46 a Major Phosphorylation Site For Apoptosismentioning
confidence: 72%
“…Ser46 phosphorylation triggers the induction of apoptosis-related genes, as shown in Figure 1 phosphorylation of p53 at Ser46 by DYRK2 regulates apoptotic cell death in response to DNA damage. 1,19 Previous findings also showed that p53 was phosphorylated by PKCδ in MCF7 and U2OS cells upon exposure to genotoxic agents ( Figure 4). 7 PKCδ-mediated phosphorylation was required for the interaction of PKCδ with p53.…”
Section: Ser46 a Major Phosphorylation Site For Apoptosismentioning
confidence: 72%
“…Dual-specificity tyrosine-phosphorylation-regulated kinase 2 (DYRK2) is a Ser/Thr kinase that plays key roles in the regulation of proliferation, cell differentiation and survival [26]. DYRK2 contributes to the regulation of various signalling pathways via the phosphorylation of relevant proteins such as NFAT, p53, c-Jun, c-Myc, eIF2Bε, tau, hPXR, glycogen synthase, CRMP4, 4E-BP1, Snail, katanin and SIAH2 [26][27][28][29][30]. Several studies highlighted the importance of DYRK2 impairing the development and progression of human cancers, such as non-small cell lung cancer, esophageal adenocarcinomas, breast cancer and ovarian serous adenocarcinoma [31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…). DYRK2 is a tumour suppressor by phosphorylating a pro‐apoptotic protein p53 for inducing apoptosis‐related genes and for degrading a key protein, snail, for tumour metastasis (Nihira & Yoshida ). Collectively, DYRKs among different species and kingdoms function in a broad spectrum of cell growth and developmental processes.…”
Section: Introductionmentioning
confidence: 99%
“…For example, an extra allele of DYRK1Awas found associated with defective neural development in Down syndrome (Wegiel et al 2011), and mice with haploinsufficiency in DYRK1A showed reduced brain size and abnormal brain morphology (Fotaki et al 2002). DYRK2 is a tumour suppressor by phosphorylating a proapoptotic protein p53 for inducing apoptosis-related genes and for degrading a key protein, snail, for tumour metastasis (Nihira & Yoshida 2015). Collectively, DYRKs among different species and kingdoms function in a broad spectrum of cell growth and developmental processes.…”
Section: Introductionmentioning
confidence: 99%